Salvation from the point of view of Ibn Taymiyya - Maryam Poorrezagholi; Mohammad Moeinifar; Asghar Salimi Naveh (Religious Inquiries, 2023)
The problem of salvation—that is, the deliverance from sins—is an issue Muslim intellectuals are expected to solve. Ibn Taymiyya’s response to the problem accounts for some of the conducts of contemporary Muslims and events of the Islamic world today. Drawing on the documentary-library method and adopting a descriptive-analytic approach, we argue thatfor Ibn Taymiyya, salvation can be imagined in one of the two forms: (i) only the followers of Islam achieve salvation, and followers of other religions will achieve salvation only if they join Islam; from this we might conclude that Ibn Taymiyya believed in “religious exclusivism,” which given the principles of Islam and those of Ibn Taymiyya’s thought, can be portrayed as against religious prejudice and violence and as compatible with tolerance as well as learning from other religions—a recommendation made by Strenmark (2006, 73) for prejudiced exclusivist leaders.(ii) given the factors leading to wretchedness, such as disbelief, heresy, and polytheism, Ibn Taymiyya’s circle of salvation does not even encompass all Muslims—his salvation is limited to only one Islamic sect. This is a construal of Ibn Taymiyya’s view adopted by excommunicative (takfīrī) Salafists, to which we shall refer in this paper as “sectarian exclusivism.”